PENGARUH PENYULUHAN DENGAN MEDIA AUDIO VISUAL DAN KONVENSIONAL TERHADAP PENGETAHUAN IBU ANAK BALITA TIDAK NAIK BERAT BADAN (T1 DAN T2) DI WILAYAH PUSK. PENIMBUNG KABUPATEN LOMBOK BARAT (NTB) - Susilo Wirawan; Lalu Khairul Abdi; Ni Ketut Sri Sulendri (Jurnal Kesehatan Prima, 2014)
Abstract: Consultation intervention using audio-visual media is one of the methods that can be carried out as an effort to enhance the society especially family (i.e. housewife) to be able to play the role as an innovator in her own household. Audio-visual is the best assistive tool nowadays. Along with the rapid development of technology, consultation using audio-visual media must also be developed at this moment. Objective of this research is to know the influence of consultations using audio-visual and conventional media on the knowledge of mothers having toddlers with non-rising weight in Penimbung Public Heath Center’s operational area, West Lombok Regency. The research was carried out in Penimbung Public Health Center’s operational area i.e. Dopang Village and Gelangsar Village in approximately 6 months, from June to November 2012. This research applied the true experimental design using pretest-posttest with control group design. The population number was 91 subjects and the samples were 60 subjects. The method of consultation used was group consultation, in which the first group (20 subjects) used audio-visual media, the second group (20 subjects) used conventional media and the third group (20 subjects) were not given any treatment at all. Data was processed using the Independent Sample t-Test statistical analysis to compare the means or average score of the knowledge of mothers among the groups, both prior to the consultation and after the consultation has been carried out. Subsequently, Paired Sample t-Test statistical analysis was used to compare the average result of the pretest with the posttest in the case group and the control group.The toddlers’ ages were between 9-57 months and half of them (50%) were first born. The mothers’ occupation were mostly (88%) housewives and some of them (38.3%) have finished junior high school/its equivalent. There was no difference in the knowledge average of mothers (posttest) after consultations using audio-visual and conventional media were conducted. There was a difference in the knowledge average of mothers (posttest) after audio-visual consultation was conducted in the control group. There was an influence seen in the increase of knowledge average of mothers when compared before and after the consultations have been conducted, both in the consultation groups using audio-visual and conventional media. The frequency of consultation conducted by the nutritionist in Penimbung Public Health Center should be increased to increase the knowledge of mothers, both by using conventional and audio-visual media. Alternative consultation media should created. One of the alternatives created is audio-visual media with an enhanced format to suit the condition of the local area because the audio-visual media that is used during this research is still simple.